Effect of Drinking Labaneh Whey on Growth Performance of Broilers - Al-Dabbas, F.M.; Abu-Dieyeh, Z.H.M.; Al-Dalain, S.Y.A. (International Journal of Poultry Science, 2007)
The present study was conducted in the poultry farm of Al-Shouback University College in the campus of Al-Balqa Applied University to evaluate the effect of drinking Labaneh whey on broiler performance. Fresh labaneh whey was mixed with the drinking water of broilers at rates of 0, 25, 50 and 75%. The experimental treatments of labaneh whey were offered ad libitum during the age 4-8 weeks of lohman broilers reared in an open-sided poultry house. At the end of the experiment, the results showed that, growth rate, body gain, feed consumption, feed efficiency and dressing percentage were significantly (p<0.05) reduced of broilers supplemented with Labaneh whey in the drinking water. Cumulative mortality rate of broilers was significantly (p<0.05) increased by increasing the level of labaneh whey above 25%. These results indicated that, using the labaneh whey as a by-product feed additive in the drinking water has a significant (p<0.05) negative effect on the performance of 4-8 week-old broilers reared in an open-sided poultry house.